(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2023)
This article discusses about the importance of reforms related to the judicial sphere in the newly adopted strategy “Uzbekistan – 2030”. The main ideas, goals and directions related to the judicial sphere in the strategy “Uzbekistan – 2030” are analyzed.